2002
DOI: 10.1002/jctb.651
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bleaching Kraft mill effluents and polychlorinated phenolic compounds with ozonation

Abstract: The effect of the simultaneous use of ozone, UVA or visible light, and small quantities of Fe(II)/Fe(III) ions in solution on the degradation rate of the organic content of a bleaching Kraft mill ef¯uent was investigated. The same treatment was applied to synthetic samples of polychlorinated phenolic compounds, because these are one of the main groups of compounds found in real bleaching Kraft mill ef¯uents. In order to improve the treatment ef®ciency and to lower the cost of the process several other strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
(24 reference statements)
2
11
0
2
Order By: Relevance
“…HVACP treatments with air generate many reactive oxygen species and ozone in the discharge. Phenolic compounds are particularly known to be susceptible to ozone attack through the degradation of aromatic rings in their structure . Similar degradation of phenolic compounds after cold plasma treatments was also reported in lettuce and orange juice .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…HVACP treatments with air generate many reactive oxygen species and ozone in the discharge. Phenolic compounds are particularly known to be susceptible to ozone attack through the degradation of aromatic rings in their structure . Similar degradation of phenolic compounds after cold plasma treatments was also reported in lettuce and orange juice .…”
Section: Resultssupporting
confidence: 61%
“…Phenolic compounds are particularly known to be susceptible to ozone attack through the degradation of aromatic rings in their structure. 43,44 Similar degradation of phenolic compounds after cold plasma treatments was also reported in lettuce 45 and orange juice. 24 However, it was interesting to note that HVACP treatment significantly increased the total flavonols in grape juice in a time-dependent manner.…”
Section: Effect On Total Phenolic Flavonoid and Flavonol Contentssupporting
confidence: 71%
“…Ozone is a strong oxidizing agent with oxidation mechanism either by direct reaction with dissolved compounds or by the generated radicals depending on the pH of the solution [24]. The ozone dosage to be applied to the pulp mill effluent depends on total color and TOC content [25] and also on the presence of toxic metabolites [26].…”
Section: Ozone Treatmentmentioning
confidence: 99%
“…Models to predict the amount of ozone leaving the reactor were developed and it was concluded that it was possible to run an ozonation system without an off-gas ozone control system (off-gas ozone has to be lower than 1 ppm as legally imposed) by controlling ozone absorption. Einstein/s X TOC = 60-90% (Pérez et al 2002) Pulp and paper wastewater coming from anaerobic Thus, the ozone contactor should be high enough to guarantee gas-liquid contact since most of ozone absorption occurs in the bottom of the column; moreover, operating in countercurrent and increasing mean hydraulic retention time showed to lead to lower off-gas ozone. Similar results were attained by (El-Din and Smith 2001) when analyzed Kraft pulp mill effluents ozonation in an impinging-jet bubble column.…”
Section: Single Ozonationmentioning
confidence: 99%
“…To enhance TOC removal of a pulp and paper effluent by the O 3 /UV process, Pérez et al (2002) tested the impact of the addition of iron ions (Fe 2+ ), which will act as homogeneous catalyst. The maximum TOC removal was about 90% in 300 min of reaction.…”
Section: Ozonation Aided By Uv/h 2 Omentioning
confidence: 99%